Carotenoids and tocols content in genotypes of colored barley. (November 2020) - Suriano, Serafino; Iannucci, Anna; Codianni, Pasquale; Fares, Clara; Menga, Valeria; Russo, Mario; Marciello, Ugo; Troccoli, Antonio
Abstract: Carotenoids and tocols of 20 genotypes of colored barley divided into three groups (A, B, C) were investigated. These included 16 F8 recombinant inbred lines obtained from crosses of four parental lines: 2005 FG, K4-31, L94 and Priora. The aim of the present study was to identify, quantify and profile characterize of tocols and carotenoids. Tocols profile is characterized by the prevalence of tocotrienols on tocopherols. The α-tocotrienol was the most represented tocol isomer, contributing about 53.03% of the total content. The highest α-tocotrienol content (33.67 μg g- 1 ) was found in the blue naked parental genotype 3007 (C-Group). The most abundant carotenoid was lutein on average 86% of total followed by zeaxanthin 10% and by α-carotene 3.40%. The Priora cultivar (C-Group) was the genotype with the highest lutein content (4.10 μg g- 1 ). The study found great variability in the content of carotenoids and tocols along the lines of each group. Graphical abstract: Image 1 Highlights: Carotenoids and tocols profile characterization of 20 colored barley genotypes. Extraction made by water-saturated/butanol and acetonitrile; analyzed by HPLC. Tocotrienols were most abundant than tocopherols in all barley genotypes. Lutein was the most representative carotenoid. The best colored barley lines can be used in breeding program.